Deep Learning Renal Segmentation for Fully Automated Radiation Dose Estimation in Unsealed Source Therapy - Jackson, Price; Hardcastle, Nicholas; Dawe, Noel; Kron, Tomas; Hofman, Michael S.; Hicks, Rodney J. (Frontiers in Oncology, 2018)
Background: Convolutional neural networks have been shown to be powerful tools to assist with object detection and—like a human observer—may be trained based on a relatively small cohort of reference subjects. Rapid, accurate organ recognition in medical imaging permits a variety of new quantitative diagnostic techniques. In the case of therapy with targeted radionuclides, it may permit comprehensive radiation dose analysis in a manner that would often be prohibitively time-consuming using conventional methods. Methods: An automated image segmentation tool was developed based on 3-dimensional convolutional neural networks to detect right and left kidney contours on non-contrast CT images. Model was trained based on 89 manually contoured cases and tested on a cohort of patients receiving therapy with 177Lu-PSMA-617 for metastatic prostate cancer. Automatically generated contours were compared with those drawn by an expert and assessed for similarity based on dice score, mean distance-to-agreement and total segmented volume. Further, the contours were applied to voxel dose maps computed from post-treatment quantitative SPECT imaging to estimate renal radiation dose from therapy. Results: Neural network segmentation was able to identify right and left kidneys in all patients with a high degree of accuracy. The system was integrated into the hospital image database, returning contours for a selected study in approximately 90 seconds. Mean dice score was 0.91 and 0.86 for right and left kidneys, respectively. Poor performance was observed in 3 patients with cystic kidneys of which only few were included in the training data. No significant difference in mean radiation absorbed dose was observed between the manual and automated algorithms. Conclusion: Automated contouring using convolutional neural networks shows promise in providing quantitative assessment of functional SPECT and possibly PET images; in this case demonstrating comparable accuracy for radiation dose interpretation in unsealed source therapy relative to a human observer.